2006
DOI: 10.1038/sj.bjc.6603215
|View full text |Cite
|
Sign up to set email alerts
|

The clinical and economic benefits of capecitabine and tegafur with uracil in metastatic colorectal cancer

Abstract: Two oral fluoropyrimidine therapies have been introduced for metastatic colorectal cancer. One is a 5-fluorouracil pro-drug, capecitabine; the other is a combination of tegafur and uracil administered together with leucovorin. The purpose of this study was to compare the clinical effectiveness and cost-effectiveness of these oral therapies against standard intravenous 5-fluorouracil regimens. A systematic literature review was conducted to assess the clinical effectiveness of the therapies and costs were calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 22 publications
2
28
0
Order By: Relevance
“…Moreover, some studies have shown that capecitabine is associated with reduced costs compared with i.v. Xuorouracil/leucovorin in both the adjuvant and palliative setting (Cassidy et al 2006;Ward et al 2006), and that the majority of cost savings were due to the reduced administration costs. The additional cost of combining oxaliplatin with capecitabine instead of Xuorouracil/leucovorin (Mayer 2007) could be counterbalanced by the lower incidence of some lifethreatening adverse events, translating into reduced costs for hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some studies have shown that capecitabine is associated with reduced costs compared with i.v. Xuorouracil/leucovorin in both the adjuvant and palliative setting (Cassidy et al 2006;Ward et al 2006), and that the majority of cost savings were due to the reduced administration costs. The additional cost of combining oxaliplatin with capecitabine instead of Xuorouracil/leucovorin (Mayer 2007) could be counterbalanced by the lower incidence of some lifethreatening adverse events, translating into reduced costs for hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…31 The treatment costs for a 12-week course of capecitabine (£2132) were found to be lower than those for the tegafur/ uracil combination (£3385), the intravenous Mayo regimen (£3593), and infusional regimens on the de Gramont (£6255) and Modified de Gramont (£3485) schedules over the same treatment period. Thus, assuming equivalent efficacy (cost minimization analysis), the study supported a cost-effectiveness argument in favor of oral therapies such as capecitabine over intravenous treatments.…”
Section: Capecitabinementioning
confidence: 98%
“…Oral formulations also have advantages for physicians, providing flexibility and adaptability to tune the dosing schedule to individual patients responses based on efficacy and toxicity. Without the intensive demands on staff required by intravenous administrations, oral formulations can also increase the number of patients treated 59 and reductions in the number of hospital or clinic visits could reduce overall costs 6063 .…”
Section: Importancementioning
confidence: 99%